2008
DOI: 10.1097/inf.0b013e3181757b16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiologic Characteristics of Human Bocavirus in Danish Infants

Abstract: Asymptomatic carriage of HBoV is common in infants <1 year of age, and an HBoV-positive test result does not imply that HBoV is the cause of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
101
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 29 publications
12
101
1
5
Order By: Relevance
“…21,27,28,64 Studies of nasopharyngeal samples have shown persistence of HBoV1 DNA for several months. [65][66][67][68] HBoV1 seroprevalence ranges from 25% in infants younger than 1 year to 93% and 100% in children of 3 (ref. 28) to 7 (ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,27,28,64 Studies of nasopharyngeal samples have shown persistence of HBoV1 DNA for several months. [65][66][67][68] HBoV1 seroprevalence ranges from 25% in infants younger than 1 year to 93% and 100% in children of 3 (ref. 28) to 7 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Other reasons for PCR negativity may be the short duration of HBoV1 viremia, as well as the fact that these children may not have had respiratory infections due to their separation from other children (especially day-care) during the chemotherapy and HSCT. 66 In this study the incidences of B19V, PARV4 and HBoV1 viremias were evaluated using quantitative real-time PCR techniques in a pediatric HSCT cohort. One-third of the patients were PCR positive for B19V without correlation with clinical symptoms (including anemia).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the present study also support the notion that HRV infection is common among the human population. HBoV pathogenesis has been a recent subject of contention; a birth cohort longitudinal study of Danish children detected HBoV frequently in both symptomatic and asymptomatic infants (3,14). In the present study, the pathogenic potential of HBoV in infants with no underlying diseases was unclear.…”
mentioning
confidence: 61%
“…In one of study, Caccia et al 18 reported that HBoV positivity was found in children with respiratory infections who had underlying risk factors as heart disease. In another study, maternal smoking and being born in winter season were found to be associated with HBoV infection 19 .…”
Section: Discussionmentioning
confidence: 99%